2016
DOI: 10.1534/genetics.116.191783
|View full text |Cite
|
Sign up to set email alerts
|

Editing Transgenic DNA Components by Inducible Gene Replacement in Drosophila melanogaster

Abstract: Gene conversions occur when genomic double-strand DNA breaks (DSBs) trigger unidirectional transfer of genetic material from a homologous template sequence. Exogenous or mutated sequence can be introduced through this homology-directed repair (HDR). We leveraged gene conversion to develop a method for genomic editing of existing transgenic insertions in Drosophila melanogaster. The clustered regularly-interspaced palindromic repeats (CRISPR)/Cas9 system is used in the homology assisted CRISPR knock-in (HACK) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
151
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 47 publications
8
151
1
Order By: Relevance
“…Inhibiting Pruning in MB ɣ Neurons Affects APL Remodeling In order to conduct the reciprocal experiment, where pruning of MB ɣ neurons is inhibited while visualizing the concurrent effects on APL development, we used a second binary system, the QF2-QUAS system (Potter et al, 2010), together with the Gal4/UAS system. We first confirmed that the GMR71G10-QF2 G4H driver (hereafter named 71-QF2) (Lin and Potter, 2016) recapitulated the GMR71G10-Gal4 expression pattern throughout development ( Figures 3A, 3C, and data not shown). Next, we used this 71-QF2 to drive the expression of QUAS-EcR DN in MB ɣ neurons and confirmed that it indeed inhibited remodeling ( Figures 3B and 3D left).…”
Section: Mb ɣ Neuron Developmental Remodeling Is Independent Of the Asupporting
confidence: 59%
“…Inhibiting Pruning in MB ɣ Neurons Affects APL Remodeling In order to conduct the reciprocal experiment, where pruning of MB ɣ neurons is inhibited while visualizing the concurrent effects on APL development, we used a second binary system, the QF2-QUAS system (Potter et al, 2010), together with the Gal4/UAS system. We first confirmed that the GMR71G10-QF2 G4H driver (hereafter named 71-QF2) (Lin and Potter, 2016) recapitulated the GMR71G10-Gal4 expression pattern throughout development ( Figures 3A, 3C, and data not shown). Next, we used this 71-QF2 to drive the expression of QUAS-EcR DN in MB ɣ neurons and confirmed that it indeed inhibited remodeling ( Figures 3B and 3D left).…”
Section: Mb ɣ Neuron Developmental Remodeling Is Independent Of the Asupporting
confidence: 59%
“…Therefore, to extend the genetic tool box for expression of transgenes specifically only in the bnl sources, we aimed to generate a LexA/lexO -based binary transcription system. Due to the unreliable expression patterns of bnl-GAL4 or bnl-IT.GAL4, repurposing these lines into the QF or LexA based systems using h omology a ssisted C RISPR k nock-in (HACK) (Lin and Potter, 2016) or Integrase Swappable In Vivo Targeting Element (InSITE) (Gohl et al, 2011) was unsuitable.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve specific GAL4 expression, we utilized the split-GAL4 strategy (32,33) to generate new driver lines specific to VA1d and DC3 PNs. We inserted the hemidriver p65 AD component after the last coding exons of C15, a transcription factor that is only expressed by PNs derived from the anterodorsal neuroblast (adPNs) (34), and converted Mz19-GAL4 to Mz19-GAL4 DBD using the HACK strategy (35,36). When we intersected these two components, expression of functional GAL4 was restricted to Mz19+ adPNs (VA1d and DC3) ( Fig.…”
Section: Fili Is Required In Va1d/dc3 Pns To Prevent Ectopic Targetinmentioning
confidence: 99%